1992
DOI: 10.1159/000173444
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Factor Infusion following Acute Renal Ischemia in Anesthetized Dogs

Abstract: Atrial natriuretic factor (ANF) has been shown to be effective in reversing renal functional impairments following renal ischemia. We studied the effects of a nonhypotensive intravenous ANF infusion (100ng/min × kg BW, 60 min) after 90 min unilateral renal arterial occlusion in anesthetized dogs with an intact contralateral kidney. ANF plasma levels remained unchanged in controls (group 1) and increased in ANF-infused animals (group 2) from 22 ± 3 to 552 ± 124 pg/ml. Blood pressure increased in both groups dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Tubular function was also im proved as evidenced by an increase in net tubular sodium rcabsorption. This observation has also been made in dog kidneys [Akabane et al, 1988: Klein et al. 1992].…”
Section: Therapeutic Potential Of Anp In Postischemic Arfsupporting
confidence: 65%
See 1 more Smart Citation
“…Tubular function was also im proved as evidenced by an increase in net tubular sodium rcabsorption. This observation has also been made in dog kidneys [Akabane et al, 1988: Klein et al. 1992].…”
Section: Therapeutic Potential Of Anp In Postischemic Arfsupporting
confidence: 65%
“…In general, most investigators agree that ANP infusion during the postischemic period results in an improve ment in GFR and therefore has significant thera peutic potential [Conger et al, 1989[Conger et al, . 1991Klein et al, 1992: Nakamoto et al, 1987: Pollock and Opgenorth. 1990.…”
Section: Therapeutic Potential Of Anp In Postischemic Arfmentioning
confidence: 99%
“…At the dose of ANP used in this study, localized renal vasodilation rather than systemic hypotension would be expected. In another dog model with unilateral renal arterial occlusion for 1.5 hrs, ANP infusion for 1 hr after ischemia prevented the decreases in renal clearance and blood flow, the effects of which were only limited during the infusion (17). However, repeated bolus injection of ANP after 2 hrs of renal ischemia in a unilaterally nephrectomized dog model has been reported to ameliorate acute renal failure on the first and second postischemic day (18) so as to maintain sufficient plasma ANP concentrations.…”
Section: Discussionmentioning
confidence: 94%
“…The reno-protective effect of ANP during endotoxemia could therefore be traced in the absence of renal nerves, although the improvement in the GFR value was relatively minor, considering the massive pharmacological dose of ANP employed. Recent studies show a therapeutic potential of the ANP for preserving renal function after renal ischemia [8,9]. ANP administration immediately after the ischemic insult significantly improves renal structure and function as assessed by GFR and ATP generation [9,10], the effects of which are not seen with other vasodilators such as acetylcholine [27] and nitroprusside [28].…”
Section: Discussionmentioning
confidence: 99%
“…Most often, where Et is associated with acute renal failure, it appears to be largely acute tubular necrosis [6,7]. Recent studies have reported beneficial effects of atrial natriuretic peptide (ANP) in limiting ischemic renal injury [8,9]. In animal models of acute ischemic renal damage, ANP decreases renal vascular resistance [8,10], increases renal blood flow [11,12] and consequently, increases GFR [13,14], which suggests a possible hemodynamic action of ANP in recovery from renal injury induced by an Et.…”
Section: Gram-negativementioning
confidence: 99%